Estimating groundwater contribution to transpiration using satellite-derived evapotranspiration estimates coupled with stable isotope analysis. (May 2018) - Gokool, S.; Riddell, E.S.; Swemmer, A.; Nippert, J.B.; Raubenheimer, R.; Chetty, K.T.
Abstract: The relative importance of groundwater (GW) to sustain terrestrial vegetation has been well documented. However, quantifying GW use by riparian vegetation in data scarce regions may prove to be challenging. For this purpose, we coupled evapotranspiration (ET) estimates from the satellite-based surface energy balance system (SEBS) model with stable isotope analysis, to map and quantify the contribution of GW to transpiration ( ET g ), along the lower reaches of a perennial river system, in the semi-arid north-eastern region of South Africa. Plant stem, soil, stream and GW samples were collected on 3 sampling occasions during the 2016 dry season. δ 2 H and δ 18 O values of the respective samples were measured and analysed. We found that while GW use was prevalent and increased with aridity, overall ET g was fairly minimal. During the initial stages of the dry season ET g for the study area was extremely low, approximately 0.10% of daily ET or 0.01 mm d −1 . However, as aridity increased, ET g increased to approximately 10% of daily ET or 0.30 mm d −1 . The results of these various investigations undertaken demonstrates the potential of coupling satellite-based ET approaches with stable isotope analysis, to quantify spatial and seasonal dynamics in ET g . Highlights: Coupling stable isotopes and satellite-derived ET to quantify water use dynamics. This enabled seasonal and spatial variations in water use dynamics to be quantified. Riparian vegetation predominantly used deeper soil water during the dry season. Groundwater use during transpiration was fairly minimal but increased with aridity.